Pharmacogenomics in oncology care - Filipski, Kelly K.; Mechanic, Leah E.; Long, Rochelle; Freedman, Andrew N. (Frontiers in Genetics, 2014)
Cancer pharmacogenomics have contributed a number of important discoveries to current cancer treatment, changing the paradigm of treatment decisions. Both somatic and germline mutations are utilized to better understand the underlying biology of cancer growth and treatment response. The level of evidence required to fully translate pharmacogenomic discoveries into the clinic has relied heavily on randomized clinical trials. In this review, the use of observational studies, as well as, the use of adaptive trials and next generation sequencing to develop the required level of evidence for clinical implementation are discussed.